Assistance In Packaging Innovation and Licensing of Small and Medium Enterprises and Young Entrepreneurs at IAIN Ponorogo - Faizin, Moh; Hasan Wahid, Soleh (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2022)
One of the factors for the lack of entrepreneurs is poor entrepreneurship skills. Most only learn marketing by self-taught, so many novice entrepreneurs fail and stop in the middle of the road. Based on initial observations of common phenomena in society, there are obstacles faced, including the inability to make product packaging that can increase the attractiveness of potential consumers. On the other hand, they also do not know how to develop a business to obtain a business license from the relevant agency. This service aims to develop innovative product design capabilities that are effective for businesses run by young entrepreneurs around IAIN Ponorogo and to train skills in business licensing for young entrepreneurs around IAIN Ponorogo. The method in this service uses the ABCD method, using data collection techniques in the form of observation, interviews, and documentation. This service found that the community was helped by implementing product design training and assistance for PIRT permits.